2017
DOI: 10.4049/jimmunol.1502532
|View full text |Cite
|
Sign up to set email alerts
|

Activated Microglia Desialylate and Phagocytose Cells via Neuraminidase, Galectin-3, and Mer Tyrosine Kinase

Abstract: Activated microglia can phagocytose dying, stressed, or excess neurons and synapses via the phagocytic receptor Mer tyrosine kinase (MerTK). Galectin-3 (Gal-3) can cross-link surface glycoproteins by binding galactose residues that are normally hidden below terminal sialic acid residues. Gal-3 was recently reported to opsonize cells via activating MerTK. We found that LPS-activated BV-2 microglia rapidly released Gal-3, which was blocked by calcineurin inhibitors. Gal-3 bound to MerTK on microglia and to stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 45 publications
9
112
0
Order By: Relevance
“…During classical microglial activation, LPS can significantly reduce MFGE8 expression (Fig 4C,D) while increasing phagocytic activity (Fig 4F). This is consistent with other past reports performed under WT conditions 18, 19, 20…”
Section: Resultssupporting
confidence: 94%
“…During classical microglial activation, LPS can significantly reduce MFGE8 expression (Fig 4C,D) while increasing phagocytic activity (Fig 4F). This is consistent with other past reports performed under WT conditions 18, 19, 20…”
Section: Resultssupporting
confidence: 94%
“…However, this has not previously been investigated in microglia. Previously, we have shown that BV‐2 microglia present a desialylating activity on their cell surface when stimulated with the TLR‐4 agonist LPS (Nomura et al, ). In this study, we show that primary microglia activated by LPS, Aβ, TAU or PMA have increased surface sialidase activity and a substantial desialylation of the surface.…”
Section: Discussionmentioning
confidence: 96%
“…This indicates that CD11b is involved in the removal of neurons from primary cultures by desialylated microglia. However, it is important to note that desialylation (of neurons or microglia) can activate microglial phagocytosis of neurons or neuronal parts (neurophagy) by multiple potential mechanisms, including: (a) increased deposition and activity of complement C1q and C3b (Linnnartz et al, ), (b) increased binding of opsonin galectin‐3 (Nomura et al, ), (c) decreased trans‐activation of inhibitory Siglec‐11 (Wang & Neumann, ), Siglec‐F (Wielgat & Braszko, ) and Siglec‐E (Claude, Linnartz‐Gerlach, Kudin, Kunz, & Neumann, ), and (d) possibly decreased cis‐activation of inhibitory Siglec‐2 (CD22; Pluvinage et al, ) and Siglec‐3 (CD33; Bradshaw et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successive recruitment of the second messenger SHP1 dephosphorylates the intracellular immunoreceptor tyrosine‐based activation motif (ITAM), thus limiting a number of downstream pathways linked to the phagocytosis of neurites and NADPH oxidase (NOX2)‐mediated production of ROS (Fig ; Graham et al, ; Hamerman et al, ). Under pathological conditions, immune cells secrete neuraminidases which cleave sialic acid residues on neurons (Amith et al, ; Pshezhetsky & Hinek, ; Nomura et al, ). Desialylated neurons are consequently opsonized by complement component C1q, which is produced and secreted by microglia (Linnartz et al, ; Madeira et al, ).…”
Section: Targeting Mononuclear Phagocytes In Retinal Degenerative Dismentioning
confidence: 99%